Environmental management accounting practices on environmental performance among students and lecturers - Abdullah, Nuraini Rasyidah; Mohd Fuzi, Nursyazwani; Che Hashim, Hanini Ilyana; Yee Ong, Sharon Yong (Human Resource Management Academic Research Society, 2023)
The purpose of the study was to investigate the perception of environmental management accounting practices on environmental performance among students and lecturers in Faculty of Management. This research was conducted using a quantitative approach. 120 questionnaires were used to collect data from students and lecturers in the Faculty of Management. The results show that monetary EMA and physical EMA have a positive impact on environmental performance. Thus, Faculty of Management should consider adopting environmental management accounting practices and using the information developed by environmental management accounting practices to achieve the greatest benefit, especially cost savings.